2022
DOI: 10.3389/fpain.2022.861598
|View full text |Cite
|
Sign up to set email alerts
|

CGRP Administration Into the Cerebellum Evokes Light Aversion, Tactile Hypersensitivity, and Nociceptive Squint in Mice

Abstract: The neuropeptide calcitonin gene-related peptide (CGRP) is a major player in migraine pathophysiology. Previous preclinical studies demonstrated that intracerebroventricular administration of CGRP caused migraine-like behaviors in mice, but the sites of action in the brain remain unidentified. The cerebellum has the most CGRP binding sites in the central nervous system and is increasingly recognized as both a sensory and motor integration center. The objective of this study was to test whether the cerebellum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 91 publications
(141 reference statements)
0
15
0
Order By: Relevance
“…However, the precise sites of CGRP action in the central nervous system that contribute to migraine attacks remain to be fully elucidated. Recent studies have presented the posterior thalamus (Sowers et al, 2020 ) and the cerebellum (Wang et al, 2022a , b ) as candidate sites for CGRP action in migraine pathophysiology.…”
Section: The Cerebellum Contains Cgrp and Abundant Cgrp Binding Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the precise sites of CGRP action in the central nervous system that contribute to migraine attacks remain to be fully elucidated. Recent studies have presented the posterior thalamus (Sowers et al, 2020 ) and the cerebellum (Wang et al, 2022a , b ) as candidate sites for CGRP action in migraine pathophysiology.…”
Section: The Cerebellum Contains Cgrp and Abundant Cgrp Binding Sitesmentioning
confidence: 99%
“…Based on the expression of CGRP receptor subunits RAMP1 and CLR in the MN (Warfvinge and Edvinsson, 2019 ), a recent study investigated the effect of CGRP delivery into the MN on migraine-like behaviors (Wang et al, 2022b ). CGRP administration into the MN induced light-aversive behavior in both male and female mice, significant anxiety-like and squinting responses in female mice and more robust tactile hypersensitivity in female mice (Wang et al, 2022b ). This discovery suggests that CGRP can act in the cerebellum to induce migraine-like behaviors (Wang et al, 2022b ).…”
Section: Animal Studies On the Cerebellum And Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, stimulation of MN CGRP neurons led to light aversion in female mice, and significant tactile hypersensitivity in ipsilateral hind paws in both sexes. A previous publication reported that direct injection of CGRP into the MN induced light aversion in both sexes, anxiety and squinting behavior in female mice, and more robust contralateral cutaneous allodynia in females than males ( Wang et al, 2022 ). Interestingly, with both studies, the responses tended to be more predominant in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the MN, specifically CGRP and its receptors in the MN, may be associated with migraine pathophysiology. A previous study has demonstrated that CGRP injections into the MN induced migraine-like behaviors, including light aversion, anxiety-like, cutaneous allodynia and nociceptive squinting behaviors ( Wang et al, 2022 ). Due to the CGRP distribution in the MN, we pursued the idea of the CGRP-expressing neurons of the MN (MN CGRP ) being involved in migraine pathophysiology.…”
Section: Introductionmentioning
confidence: 99%